Ethical Complexities of Classroom and Professional Life: the case of gossip - White, Patricia (Revista Internacional de Teoría e Investigación Educativa, 2024)
An examination of five examples of gossiping within a school context casts doubt on the general view of gossip as either reprehensible or trivial. A discussion of the examples highlights an area of largely unexamined ethical complexity in the teacher’s professional life. It reminds us that gossip can promote the goods of solidarity and collegiality, it can be a help to moral deliberation and be instrumental in the uncovering of systemic moral flaws in the workings of the institution. It concludes that gossiping can be permissible and that sometimes, in an ethically complex situation, teachers may decide that it is their professional duty to gossip.